Improvement of Mechanical Ductile Properties of Poly(3‐hydroxybutyrate) by Using Vegetable Oil Derivatives. Issue 2 (4th November 2016) - Garcia‐Garcia, Daniel; Fenollar, Octavio; Fombuena, Vicent; Lopez‐Martinez, Juan; Balart, Rafael
Abstract : The effect of maleinized linseed oil and an epoxidized fatty acid ester on mechanical and thermal properties of poly(3‐hydroxybutyrate) has been evaluated. The results show that a small addition of both plasticizers (5 phr) provides increased elongation at break values together with a remarkable increase in the impact resistance and, subsequently, toughness improvement. Abstract : Poly(3‐hydroxybutyrate), P3HB is a thermoplastic polyester synthesized from bacterial fermentation with potential uses in packaging due to its biodegradability. Nevertheless, P3HB is a fragile material and its processing temperature window is very narrow which restricts its use. This study explores the potential of vegetable oil‐derived plasticizers, i.e., maleinized linseed oil (MLO) and an epoxidized fatty acid ester (EFAE) in the 5–20 phr range as environmentally friendly solutions for P3HB industrial formulations with improved toughness. The results show that optimum balance between ductile properties is achieved with low plasticizer content (5 phr) for both plasticizer types. Elongation at break and the impact resistance are increased by 28 and 71% respectively after addition of 5 phr MLO. With regard to EFAE, the elongation at break is improved by 40% and the impact resistance is increased to twice the value of P3HB. Another effect that both plasticizers provide is the thermal stabilization with a delay in the onset degradation temperature.